Production of Methanol from coco gas - Giongco, Ditas V. (College of Engineering, 1975)
This is a report on the study of the feasibility of a methanol plant operating in the intermediate pressure range using coco gas as the starting material. -- Capacity: 150 tons/day -- Land area: 6000 sq meters -- Fixed capital: P 20,432,218 -- Total product cost: P 13,625,621 -- Annual sales: P 19,084,505 -- Gross profit: P 5,461,884 -- Pay-out time: 2.72 years -- Break-even point: 40% of max. cap.